(untitled) (International Journal of Medicine and Medical Sciences, 2020)
The present study was performed to evaluate the anti-ulcerogenic activity of hyaluronic acid against ethanol induced gastric mucosal injury in rats. Four groups of adult Sprague Dawley rats were orally pre-treated respectively with distilled water (ulcer control groups), omeprazole (reference group), high molecular weight hyaluronic acid and 0.8% hyaluronic acid gel (experimental groups) one hour before oral administration of absolute ethanol to generate gastric mucosal. After an additional hour, the rats were sacrificed and the ulcer areas of the gastric walls were determined. Grossly, the ulcer control group exhibited severe mucosal injury, whereas pre-treatment with omeprazol, and both types of hyaluronic acid gel, exhibited significant protection of gastric mucosal injury. Histological studies of the gastric wall revealed that ulcer control group exhibited severe damage of gastric mucosa; along with edema and leucocytes infiltration of submucosal layer compared to rats pre-treated with hyaluronic acid gels which showed comparatively gastric mucosal protection, reduction or absence of edema and leucocytes infiltration of submucosal layer. The present finding suggests that high molecular weight hyaluronic acid gel promotes higher ulcer protection.